Looking for alaska ebook - Green, John (2008)
The award-winning, genre-defining debut from John Green, the #1 bestselling author of The Anthropocene Reviewed and The Fault in Our Stars Winner of the Michael L. Printz Award • A Los Angeles Times Book Prize Finalist • A New York Times Bestseller • A USA Today Bestseller • NPR’s Top Ten Best-Ever Teen Novels • TIME magazine’s 100 Best Young Adult Novels of All Time • A PBS Great American Read Selection • Millions of copies sold!   First drink. First prank. First friend. First love. Last words.   Miles Halter is fascinated by famous last words—and tired of his safe life at home. He leaves for boarding school to seek what the dying poet François Rabelais called the “Great Perhaps.” Much awaits Miles at Culver Creek, including Alaska Young, who will pull Miles into her labyrinth and catapult him into the Great Perhaps. Looking for Alaska brilliantly chronicles the indelible impact one life can have on another. A modern classic, this stunning debut marked #1 bestselling author John Green’s arrival as a groundbreaking new voice in contemporary fiction. Newly updated edition includes a brand-new Readers' Guide featuring a Q&A with author John Green